Analisis Respon Peserta didik terhadap Penggunaan Media Pembelajaran Berbasis Multimedia di SDN 008 Pulau Lancang - Dita Maisurah (Universitas Muhammadiyah Enrekang, 2023)
By enhancing student success and desire to study, learning media play a critical part in making the teaching and learning process more engaging. When creating learning materials for students, multimedia-based learning media may include text, graphics, audio, video, animation, and other sorts of media. The use of multimedia in the classroom may increase students' engagement in the learning process by facilitating a deeper understanding and absorption of the subject. This essay seeks to ascertain how students at SDN 008 Pulau Lancang feel about the utilization of multimedia-based learning materials. This form of study includes questionnaires or questionnaires with 4 categories, including Strongly Disagree (STS), Disagree (ST), Agree (S), and Strongly Agree (SS), with 15 statements filled out by 30 students as respondents.